2012
DOI: 10.1155/2012/576584
|View full text |Cite
|
Sign up to set email alerts
|

HOMA-AD in Assessing Insulin Resistance in Lean Noncirrhotic HCV Outpatients

Abstract: Introduction. There is an association between HCV and insulin resistance (IR), which is currently assessed by HOMA-IR. There is evidence that HOMA-adiponectin (HOMA-AD) is more accurate, but its role in HCV patients is unknown. The purpose of this study was to evaluate IR in an HCV sample and controls, in order to compare the accuracy of HOMA-IR and HOMA-AD. Methods. Ninety-four HCV outpatients aged <60 years who met the criteria of nondiabetic, nonobese, noncirrhotic, and nonalcohol abusers were included and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…More recently, a study conducted in the general Japanese population proposed the Homeostasis Model Assessment–Adiponectin (HOMA-AD) index, a modified version of the model, which incorporates the total serum adiponectin level in the denominator of the index and, consequently, it adds an indirect measurement of adiposopathy [ 6 ], and ultimately an adjustment to the individual degree of adiposity. Subsequently, studies with obese children [ 7 ] and with chronic hemodialysis patients [ 8 ] have also identified the good performance of the HOMA-AD index, whereas one study with lean non cirrhotic HCV outpatients did not detect any benefit when comparing the HOMA-AD with the HOMA1-IR [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a study conducted in the general Japanese population proposed the Homeostasis Model Assessment–Adiponectin (HOMA-AD) index, a modified version of the model, which incorporates the total serum adiponectin level in the denominator of the index and, consequently, it adds an indirect measurement of adiposopathy [ 6 ], and ultimately an adjustment to the individual degree of adiposity. Subsequently, studies with obese children [ 7 ] and with chronic hemodialysis patients [ 8 ] have also identified the good performance of the HOMA-AD index, whereas one study with lean non cirrhotic HCV outpatients did not detect any benefit when comparing the HOMA-AD with the HOMA1-IR [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…IR was not associated with fibrosis grade as was observed in studies conducted in HCV patients from Northeast and South regions of Brazil (9,14); this could be because of the small number of patients with an advanced grade of fibrosis that was included in these studies.…”
Section: Discussionmentioning
confidence: 64%
“…In Brazil, IR prevalence varies from 20 to 80% in HCV patients (9)(10)(11)(12)(13). IR was also associated with age, waist circumference, body mass index (BMI), advanced liver fibrosis (10), HCV viral load (14), higher mean degree of steatosis (15) and higher serum levels of oxidative stress (10,11). Although some studies have reported IR prevalence among HCV individuals, the number of subjects is relatively small, and only one or two HCV genotypes were included.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the present study is the first to assess insulin sensitivity in overweight adults with LBW. HOMA-AD has been evaluated in the pediatric population, individuals with chronic kidney disease and chronic liver disease (36)(37)(38). We also calculated TG/HDL ratio, an alternative, low-cost, useful index for clinical practice.…”
Section: Discussionmentioning
confidence: 99%